وجهة النظر ودورها في تشكيل المكان دراســة في رواية ((باب الســاحة)) للكاتبة (( ســحر خـليفة )) - الشـامي, حسـان (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يحاول هذا البحث تقديم قراءة تطبيقية لمفهوم وجهة النظر((Point Of View)) بوصفه أحد أبرز التقنيات السردية المؤثرة في بناء الرواية ، وفي تحديـد طبيعـة الخطاب الـروائـي ، وتشــكيل المكان ، وبيان صفاتـه ودلالاته تـبعاً لمنظور الـراوي أو الشخصية وموقع كل منهما مما يرويه. ويبدو تأثير وجهة النظر في روايـة ((باب الســاحة)) جـلياً وفـعّالاً فـي تجســيد المكان الروائي، ومنحه أبعاده الفنية والفكرية والجمالية، فعلاقة الراوي بالمكان ليسـت عابرة أو سـطحية، بل علاقة مترابطة جدلية تقوم على التأثر والتأثير وهي حيوية للكشف عن أبعاد الشخصيات ومكنوناتها، وكذلك عن صفات المكان ودلالاته. وتختلف هذه العلاقة قرباً أو بعداً، انســجاماً أو نفوراً، وتتسم في معظم الأحيان بالتبادلية، فالمكان يتأثر بالتغيّرات والتحولات الاجتماعية، وسواها، كما يؤثر فيها تبعاً لسـيرورة الأحداث، وطبيعة الشخصيات، ومن هنا يبدو تشــكيل المكان، وفق مستوى الرؤية ، وسيلة فنية وجمالية، لاكتشاف رؤية الكاتبة لعالمها الروائي. The research tries to present an applied reading for the concept of “Point of View”, being described as one of the most prominent narration techniques that affect the construction of the novel, in determining the nature of narrative speech, the formation of the scene, and showing its qualities and indications from the Narrator’s or Character’s prospect and the position of each of them regarding what is narrated. The effect of the “Point of View” in the Novel “BAB ALSAHA” seems quite clear and efficient in the incarnation of the Novel Scene and in granting it technical, intellectual and aesthetic dimensions. The relation of the Narrator to the Scene is not transient or superficial, but it is a coherent and dialectic relation based on giving effect and getting effect. It is vital in revealing the dimensions and constituents of the Characters, and also the characteristics of the Scene and its indications. This relation differs in being close or distant, in harmony or in repulsion. Sometimes it is reciprocal. The Scene is affected by the social changes and conversions and others, and at the same time it may be affected by the course of the events and the nature of the characters. Hence, the formation of the Scene, according to the level of vision, seems a technical and aesthetic means to discover the Writer’s vision of her novel’s world.